Melatonin receptors in GtoPdb v.2021.3. (2021) - Cardinali, Daniel P.; Delagrange, Philippe; Dubocovich, Margarita L.; Jockers, Ralf; Krause, Diana N.; Markus, Regina Pekelmann; Olcese, James; Pintor, Jesús; Renault, Nicolas; Sugden, David; Tosini, Gianluca; Zlotos, Darius Paul
No abstract available